Effect of wetsuit use on body temperature and swimming performance during training in the pool: Recommendations for open-water swimming training with wetsuits - Fujimoto, T.; Matsuura, Y.; Baba, Y.; Hara, R. (International Journal of Sports Physiology and Performance, 2024)
Purpose: Open-water swimmers need to train with wetsuits to get familiar with them; however, body core temperature (Tcore) kinetics when using wetsuits in swimming-pool training remains unclear. The present study assessed the effects of wetsuit use in pool training on Tcore, subjective perceptions, and swimming performance to obtain suggestions for wearing wetsuits in training situations.